Political marketing alchemy the state of opinion research - Turcotte, André (Palgrave Macmillan, 2021)
Public opinion research has been under a great deal of criticism over the last few years as it failed to accurately predict a series of important outcomes around the world. As a result, polls are now assumed to be inaccurate at best, manipulative at worst. Nevertheless, corporations, the media, interest groups and politicians alike continue to rely heavily on them for guidance and strategic insights. The aim of this book is to examine the status of market intelligence in practice and how changes in its different contributing streams-media polling, commercial public opinion research and political polling-are pushing market intelligence into a new phase of development. This book suggests that we are moving to a new phase where the practice of market intelligence will be more akin to market surveillance and this field is on the verge of a major transformation. André Turcotte is an Associate Professor at the School of Journalism and Communication, Carleton University, Canada. He has worked with several polling firms over the years and has provided opinion research advice to several politicians, corporations and organizations
Chapter 1. How We Got Here -- Chapter 2. Media Polls: The Gallup Legacy -- Chapter 3. Commercial Public Opinion Research: Show Me The Money -- Chapter 4. Market Intelligence: Glamour and Grief -- Chapter 5. "Where Are We Going?" From Market Intelligence to Market Surveillance
Keywords: Elections; Political communication; Marketing; Öffentliche Meinung; Demoskopie; Politische Kommunikation